Politics and the distribution of federal funds: Evidence from federal legislation in response to COVID-19 - Stan Veuger; Jeffrey Clemens (American Enterprise Institute (AEI), 2021)
COVID-19 relief legislation offers a unique setting to study how political representation shapes the distribution of federal assistance to state and local governments. We provide evidence of a substantial small-state bias: an additional Senator or Representative per million residents predicts an additional 670 dollars in aid per capita across the four relief packages. Alignment with the Democratic party predicts increases in states' allocations through legislation designed after the January 2021 political transition. This benefit of partisan alignment operates through the American Rescue Plan Act's sheer size, as well as the formulas through which it distributed transportation and general relief funds.
Keywords: A; 330; Coronavirus; Political Economy; Political System; State And Local Budgets; State Government; Stimulus